(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2026)
This paper explores the dynamic evolution of non-governmental non-profit organizations (NGOs) in Central Asia, particularly focusing on the development of these organizations in Uzbekistan, Tajikistan, Kyrgyzstan, and Turkmenistan. Following their independence from the Soviet Union, these countries have experienced varying trajectories in the formation of civil society institutions, influenced by their political regimes, legal frameworks, and international cooperation. The development process of NGOs in Uzbekistan has seen significant growth, supported by governmental reforms and the establishment of institutional infrastructures like NGO Houses. Conversely, in Tajikistan and Turkmenistan, the NGO sector faces stricter state control, limiting their independence and political activities. This paper analyzes the stages of NGO development in these countries, highlighting both successes and challenges, and argues for context-based approaches to strengthen civil society in the region, taking into account the different political landscapes. The findings underscore the critical role of NGOs in fostering democratic practices, addressing social issues, and contributing to the overall socio-economic development of Central Asian nations.